Tradisi Siat Sambuk di Banjar Pohgending Desa Pitra Ditinjau Dari Nilai-Nilai Pendidikan Agama Hindu - Harsana, I Ketut Gede (Jayapangus Press, 2025)
This research aims to analyze the values ​​of Hindu religious education contained in the siat sambuk tradition in Banjar Pohgending, Pitra Village, Penebel District, Tabanan Regency, Bali, as well as its contribution to cultural preservation and development of the spiritual character of the community. The siat sambuk tradition, which is held every Pengerupukan Day before Nyepi, involves young people in a symbolic